PROSEDUR DALAM MELAKUKAN ANALISIS KEBUTUHAN BELAJAR WARGA BELAJAR PAKET C DI SPNF SANGGAR KEG IATAN BELAJAR KOTA BENGKULU - Sipayung, Rachel Dwi Putri; Gusti, Ririn; Palenti, Citra Dwi (Comm-Edu (Community Education Journal), 2025)
Learning needs can be interpreted as a gap between the level of knowledge, skills, or attitudes possessed at a certain time and the level of knowledge. Learning needs are skills, and or attitudes that a person, group, institution, and or community wants to acquire which can only be achieved through learning activities. There are four steps that must be taken in the learning needs analysis procedure as follows: which were put forward by Sujarwo (2020). Needs analysis is a procedure for collecting information about the needs of learners by analyzing their goals or targets, deficiencies, and desires or interests. Needs analysis is carried out to find out information about learners related to their goals in participating in the learning program. Their attitudes to learning, their previous learning experiences, regarding their preferred learning style or needs and background are also part of the information collection process. This information can be collected through various sources including institutions and through the learners themselves.